A study to assess the critical result reporting at B &C Medical College and teaching hospital - Sharma, Sujan; Koirala, Barsha; Keyal, Niraj (Journal of Pathology of Nepal, 2018)
Background: The critical value can occur while performing panels of tests at laboratory by different chemistry or blood analysers with varieties of principles. The main objective of the study was to study the process of critical result reporting and to know the way of communication and documentation done for critical value in the laboratory, ICUs and the wards. Materials and Methods: This study was prospective and non-experimental was conducted at B&C Medical College and Teaching Hospital from 14.04.2018 to 14.05.2018. Total 60 critical values samples were included. The data was collected by means of observing the critical values of inpatient and the process of reporting from the laboratory to the respective wards and ICUs. Results: Out of 60 samples included in our study, there was 100% communication to concerned treating units. For the confirmation of critical value repeat test was done in 68% of cases. In 75% of cases clinicians did follow up. Recording of a critical report in lab was done in 96% of cases and almost all of the critical values 98% were immediately reported to the respective wards by technical staffs. There was no communication in 1.6% of cases to treating units by technical staff. Majority 78% of critical values were communicated by respective wards and ICUs nurses to concerned doctors. Conclusion: Critical value can occur while performing panels of tests at laboratory and reporting such values to treating clinicians or respective wards or ICUs could help heath care providers for effective treatment of the patients and their adequate care.